Primary Diffuse Large B Cell Lymphoma Mimicking Hyperplastic Reactive Lesion (Lymphoma of the Oral Cavity) - Liziane Cattelan Donaduzzi; Angélica Reinheimer; Maria Augusta Ramires da Silva; Lucia de Noronha; Aline Cristina Batista Rodrigues Johann; Ademir Franco; Soraya de Azambuja Berti Couto; Paulo Henrique Couto Souza (Hindawi Limited, 2018)
Objective. To report a case of a challenging oral diagnosis involving a primary diffuse large B cell lymphoma of the oral cavity mimicking a hyperplastic reactive lesion. Case Report. A 72-year-old male patient was referred to the Department of Stomatology presenting a proliferative nodular lesion in the anterior region of the mandible involving the anterior teeth. The clinical examination revealed anterior teeth affected by periodontal disease, suggesting the nodular cession hyperplastic reaction. Incisional biopsy was performed under local anesthesia. The histopathological examination revealed a diffuse proliferation of atypical large lymphoid cells. The tumor cells showed immunopositivity for CD20 and Ki67 (100%) and negativity for CD3, CD30, and CD15. The diagnosis of diffuse large B cell lymphoma was established. The patient underwent chemotherapy and progressed to death after nine months. Conclusion. Lymphomas of the oral cavity are rare and may have nonspecific clinical features, mimicking inflammatory and reactive lesions. Therefore, a detailed clinical evaluation associated with histopathological and immunohistochemical analysis should be performed to enable early and accurate diagnoses in suspected oral lesions.